How is ‘cooperation’ promoted in a 1st-semester English course in the Foreign Languages program at University of Valle? (2023)
This work investigates the promotion of cooperation in a 1st-semester English course within the Foreign Languages program at the University of Valle. The research questions explore the strategies employed to foster cooperation, the characteristics of cooperative learning conducive to communicative competence development, and the methodologies applied in the English as a Foreign Language (EFL) virtual classroom. The methodology involves a case study with class observations, student interviews, and document analysis, including the examination of the class syllabus. The findings reveal that students can also be engaged in group tasks and virtual discussions, demonstrated enhanced communicative competence. The teacher's use of familiar topics facilitated student connection, encouraging the expression of experiences and opinions. Task-based learning emerged as a methodology promoting cooperation, providing students the opportunity to collaborate and assist each other in task completion. Cooperation, conceptualized as small-group work involving knowledge exchange and idea sharing, resulted in the creation of language pieces, fostering constant communication and improving language skills. This study underscores the importance of cooperation in language learning, emphasizing its role in developing communicative competence and enriching the overall learning experience in the EFL virtual classroom.